An institution of higher education in teacher training: a metaphor built within - Duarte, Pedro; Diogo, Fernando (Universidade Estadual de Campinas, 2018)
The present work aims, through the analysis of 32 surveys, to verify the possibility of constructing an explanatory metaphor, based on the perspective of the respondents. It is intended, rather than giving an external view of the Institution of Higher Education Teacher Training under analysis, to perceive the perspective of the different elements that compose it. Thus, in the initial phase, it was decided to briefly explore the different perspectives and possible visions of the school and educational organizations. In order to develop this process,traditional models / metaphors of organizational analysis were used. At a later stage, the data from the surveys were explored to verify that significant trends could serve as a basis for (re) constructing a metaphor that explains the functioning of the Institution of Higher Education for Teacher Education studied. The analysis, taking into account the number of sample elements and the data collection instrument used, was essentially based on a quantitative perspective. In the final phase, and in the face of two previous aspects, it is proposed ametaphor that is able to explain, based on the perspective of the respondents, a way in which a higher education institution of Teacher Training structures, organizes and functions: School as Tree House.